A Regularization Scheme for 2D Conductivity Imaging by the D-Bar Method. (10th September 2019) - El Arwadi, Toufic; Sayah, Toni
Abstract: This article deals with the D-bar method in order to determine the conductivity distribution inside a body from the electrical measurements at the boundary. We introduce a new algorithm called t m B regularization which allows us to get a high order error estimates. Then we prove the stability of the corresponding method and we treat the case of nonsmooth conductivities.